Governance and development in India: a comparative study on Andhra Pradesh and Bihar after liberalization - Zarhani, Seyed Hossein (Routledge, 2018)
Introduction: puzzle of divergent development trajectories within a debated (non)-developmental state -- State of art : governance and comparative political economy -- Theoretical framework -- Elite agency and development in Andhra Pradesh (I) : confrontation and populism in the age of tollywood superstar -- Elite agency and development in Andhra Pradesh (II) : pragmatism, cooperation and pro-growth policies in era of the CEO of Andhra Pradesh -- Elite agency and development in Bihar (I) : confrontation and populism in era of gharibon ka masiha -- Elite agency and development in Bihar (II) : pragmatism, cooperation, and reforms in the era of sushasan babu -- Conclusion: a transformed institutional arrangement, rational regional leaders, and development.
Includes bibliographical references and index
Keywords: India -- Politics and government; Electronic books; Wirtschaftsentwicklung; Corporate Governance; Andhra Pradesh; Bihar; Entwicklungspolitik; Elite; Politische Steuerung; Indien